2020
DOI: 10.4269/ajtmh.20-0479
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Thiamin Diphosphate High-Performance Liquid Chromatography and Erythrocyte Transketolase Assays for Evaluating Thiamin Status in Malaria Patients without Beriberi

Abstract: Thiamin deficiency, or beriberi, is an increasingly re-recognized cause of morbidity and mortality in the developing world. Thiamin status has traditionally been measured through the erythrocyte activation assay (ETKA) or basal transketolase activity (ETK), which indirectly measures thiamin diphosphate (TDP). Thiamin diphosphate can also be measured directly by high-performance liquid chromatography (HPLC), which may allow a more precise estimation of thiamin status. We compared the direct measurement of TDP b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Basal ETK activity is reported to be more closely related to ThDP than ETKac, 18 possibly because of the potential ambiguity in activity coefficients when apoenzyme levels are low, and was observed to better predict infantile beriberi than ETKac. 17 Other studies have reported that ETKac provides a more robust and sensitive marker of thiamine status.…”
Section: Uk (B) (A)mentioning
confidence: 97%
See 2 more Smart Citations
“…Basal ETK activity is reported to be more closely related to ThDP than ETKac, 18 possibly because of the potential ambiguity in activity coefficients when apoenzyme levels are low, and was observed to better predict infantile beriberi than ETKac. 17 Other studies have reported that ETKac provides a more robust and sensitive marker of thiamine status.…”
Section: Uk (B) (A)mentioning
confidence: 97%
“…Mothers in Laos had a mean basal ETK activity of 0.58 U/gHb. 17 A number of other studies performed in Laos reported values in malaria-infected patients 18,19 and in infants with 17 and without 17,44 clinical signs of thiamine deficiency.…”
Section: Uk (B) (A)mentioning
confidence: 99%
See 1 more Smart Citation
“… 18 A recent study of children and adults found that while both basal and ETKAC correlated with erythrocyte ThDP, the correlation was stronger for basal activity. 19 Basal (or activated ETK) activity needs to be expressed per mass unit of hemoglobin, and it is necessary to measure the hemoglobin concentration in the same lysate as used for the ETK activity assay. In addition, it is necessary to calculate the factor needed to convert rate to activity.…”
Section: Calculation and Interpretation Of The Etkacmentioning
confidence: 99%
“…However, the use of basal ETK activity rather than ETKAC has also been recommended, particularly for the assessment of thiamine status in infants due to potential low levels of apoenzyme caused by long‐term low exposure to thiamine 18 . A recent study of children and adults found that while both basal and ETKAC correlated with erythrocyte ThDP, the correlation was stronger for basal activity 19 . Basal (or activated ETK) activity needs to be expressed per mass unit of hemoglobin, and it is necessary to measure the hemoglobin concentration in the same lysate as used for the ETK activity assay.…”
Section: Calculation and Interpretation Of The Etkacmentioning
confidence: 99%